(untitled) (Psicologia: Teoria e Pesquisa, 2011)
This study aimed to investigate the pattern of adherence of caregivers of HIV seropositive children and adolescents and to identify the coping strategies against the stressors of seropositivity. The 30 caregivers that participated in the study responded to a semi-structured interview and a scale of how to cope with problems. A clinical record was used as a secondary data source. The caregivers were classified in an adhesion group (n=25) and non-adhesion group (n=5), based on their behavior related to the use of antiretroviral medicaments and other criteria. No significant differences were found in coping strategies between the groups, except in the strategy based on religiosity/fantasy thinking. The results provide a basis for interventions aimed at reducing psychosocial impacts of HIV.